Organizational support and psychological empowerment in shaping readiness for change under kampus berdampak reform - Neka Erlyani; Rika Vira Zwagery; Salsabila Harfi Alifya (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
The implementation of the Kampus Berdampak policy introduces substantial organizational changes that require the active involvement of educational support personnel (ESP), whose readiness for change remains relatively underexplored despite their strategic role in higher education transformation. This study examines the influence of perceived organizational support, psychological empowerment, and affective commitment on readiness for change among ESP in private higher education institutions (PHEIs) in South Kalimantan. Using a quantitative explanatory design, data were collected from 207 educational support personnel across several private universities through validated and reliable Likert-scale questionnaires. The data were analyzed using multiple linear regression analysis. The results indicate that perceived organizational support, psychological empowerment, and affective commitment jointly have a significant effect on readiness for change (R² = 0.542), with psychological empowerment emerging as the strongest predictor. These findings suggest that readiness for change is shaped not merely by formal policy mandates but also by employees’ perceptions of autonomy, competence, and organizational support in their daily work environment. This study contributes to the readiness for change literature by situating the analysis within a policy-driven higher education reform context and offers practical implications for strengthening empowerment-oriented human resource practices to support the effective implementation of the Kampus Berdampak policy.